Adolescent Reproductive Knowledge, Attitudes, and Beliefs and Future Fatherhood - Garfield, Craig F. (J Adolesc Health, 2016)
BACKGROUND: With a growing focus on the importance of men’s reproductive health--including preconception health--the ways in which young men’s knowledge, attitudes, and beliefs (KAB) predict their reproductive paths are understudied. OBJECTIVE: To determine if reproductive KAB predicts fatherhood status, timing and residency (living with child or not). METHODS: Reproductive KAB and fatherhood outcomes were analyzed from the National Longitudinal Study of Adolescent Health, a 20-year, nationally representative study of individuals from adolescence into adulthood. Four measures of reproductive KAB were assessed during adolescence in Waves I and II. A generalized linear latent and mixed model predicted future fatherhood status (non-father, resident/nonresident father, adolescent father) and timing while controlling for other socio-demographic variables. RESULTS: Of the 10,253 males, 3425 were fathers (686 non-resident/2739 resident) by wave IV. Higher risky sexual behavior scores significantly increased the odds of becoming nonresident father (OR=1.30, p < 0.0001), resident father (OR=1.07, p = 0.007), and adolescent father (OR=1.71, p < 0.0001); higher pregnancy attitudes scores significantly increased the odds of becoming a nonresident father (OR=1.20, p < 0.0001) and resident father (O =1.11, p < 0.0001); higher birth control self-efficacy scores significantly decreased the odds of becoming a nonresident father (O =0.72, p < 0.0001), and adolescent father (OR=0.56, p = 0.01). CONCLUSION: Young men’s KAB in adolescence predicts their future fatherhood and residency status. Strategies that address adolescent males' reproductive KAB are needed in the prevention of unintended reproductive consequences such as early and nonresident fatherhood.